Effect of Dimexide on Functional Characteristics of Rabbit Testicular Tissue - Chadaev, V. E. (Problems of Cryobiology and Cryomedicine, 2009)
The effect of dimethyl sulfoxideÂ cryoprotectant on functional characteristics of rabbit testicular tissue has been studied. It has been established that the low concentrations of dimexide strengthen the effect of steroidogenesis stimulators, but the higher ones inhibit.